2005
DOI: 10.1007/s11302-005-1172-0
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol inhibits the effects of extracellular ATP in human sperm by a non genomic mechanism of action

Abstract: Steroid hormones, beside their classical genomic mechanism of action, exert rapid, non genomic effects in different cell types. These effects are mediated by still poorly characterized plasma membrane receptors that appear to be distinct from the classic intracellular receptors. In the present study we evaluated the non genomic effects of estradiol (17bE 2 ) in human sperm and its effects on sperm stimulation by extracellular ATP, a potent activator of sperm acrosome reaction. In human sperm 17bE 2 induced a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 48 publications
6
12
0
Order By: Relevance
“…In this work, we proposed the participation of P2X7 receptors in the AR induced by ATP of rat spermatozoa based on: (1) the AR induced by ATP is prevented by general P2 receptor inhibitors such as Suramin and oATP; (2) BzATP is 500 times more potent than ATP to induce AR; (3) the AR is prevented by 17−β‐oestradiol and BB‐G, two blockers of P2X7 ion currents in other cell types; (4) it is present in the mature spermatozoa and localized in the tail and in the acrosomal domain of the head. Our results agree with previous reports in human spermatozoa that 17‐β‐oestradiol prevents the AR induced by ATP (Foresta et al, ; Rossato et al, ). On the other hand, a previous study showed a bivalent ion current evoked by ATP in epidydimal non‐capacitated mouse spermatozoa (Navarro et al, ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In this work, we proposed the participation of P2X7 receptors in the AR induced by ATP of rat spermatozoa based on: (1) the AR induced by ATP is prevented by general P2 receptor inhibitors such as Suramin and oATP; (2) BzATP is 500 times more potent than ATP to induce AR; (3) the AR is prevented by 17−β‐oestradiol and BB‐G, two blockers of P2X7 ion currents in other cell types; (4) it is present in the mature spermatozoa and localized in the tail and in the acrosomal domain of the head. Our results agree with previous reports in human spermatozoa that 17‐β‐oestradiol prevents the AR induced by ATP (Foresta et al, ; Rossato et al, ). On the other hand, a previous study showed a bivalent ion current evoked by ATP in epidydimal non‐capacitated mouse spermatozoa (Navarro et al, ).…”
Section: Discussionsupporting
confidence: 94%
“…It has also been shown that 3 μM 17β‐oestradiol inhibits the P2X7 receptor cation current by a non‐genomic pathway and that it prevents the AR induced by ATP in human spermatozoa (Cario‐Toumaniantz et al, ; Rossato et al, ) We observed that in rat spermatozoa, 3 μM 17β‐oestradiol significantly prevented the AR in capacitated rat spermatozoa incubated with 1 μM BzATP or 500 μM ATP (Fig. C and D).…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Other cellular ligands can induce the AR such as progesterone (31, 55, 355, 506), ␥-aminobutyric acid (GABA) (280,355,559), glycine (301), EGF (133), ATP (339,442), acetylcholine (66), and sphingosine-1-phosphate (495). The role of many of these "alternative" agonists is not clear.…”
Section: A Generalitiesmentioning
confidence: 99%
“…Nevertheless, fertility of male P2X2 knockout mice declined with frequent mating over days, suggesting that P2X2 receptors add a selective advantage under these conditions. Sperm preincubation with oestradiol 17βE 2 inhibited the effects of extracellular ATP on sperm plasma membrane potential variations and the acrosome reaction [352]. Extracellular ATP improves human sperm motility parameters and provides a rational explanation for increased IVF percentages when sperm is treated with ATP [103].…”
Section: Prostatementioning
confidence: 99%